2011
DOI: 10.1186/1472-6882-11-106
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and anthelmintic potential of crude saponins isolated from Achillea Wilhelmsii C. Koch and Teucrium Stocksianum boiss

Abstract: BackgroundSaponins isolated from plant sources have a number of traditional and industrial applications. Saponins have pharmacological effects like anti-inflammatory, molluscicidal, antimicrobial, antispasmodic, antidiabetic, anticancer, anticonvulsant, anthelmintic, antitussive and cytotoxic activities. The current work describes the anthelmintic and cytotoxic activities of crude saponins of Achillea Wilhelmsii and Teucrium Stocksianum as these plants are rich with saponins.MethodsBrine shrimp cytotoxic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…Since the plant was reported to have antispasmodic activity, hence, the current work is a step forward attempt to know in which fractions the relaxant constituents concentrate. Antioxidant activity was also performed as the plant contains flavonoids, which have antioxidant activity in general [9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…Since the plant was reported to have antispasmodic activity, hence, the current work is a step forward attempt to know in which fractions the relaxant constituents concentrate. Antioxidant activity was also performed as the plant contains flavonoids, which have antioxidant activity in general [9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…Teucrium stocksianum possesses hepatoprotective and gastric cytoprotective properties [15,16]. Crude saponins isolated from it have shown cytotoxic and anthelminthic effects [17], while antispasmodic activity has also been reported recently. These scientific studies indicate high medicinal potential of T. stocksianum.…”
Section: Introductionmentioning
confidence: 99%
“…The reports indicated that the A. wilhelmsii essential oil also contains active components (Afsharypuor et al, 1996) with different biological properties such as anxiolytic (Majnooni et al, 2013), insecticide (Khani et al, 2012), cytotoxic, and anthelmintic potential (Ali et al, 2011). Our recent study indicated the in vitro antioxidant activity of A. wilhelmsii essential oils with the p-cymene, terpinolene, and a-thujene as the major compounds (Roshanaei et al, 2012).…”
Section: Introductionmentioning
confidence: 99%